Hedonic Test of Garcinia dulcis (Roxb.) Kurz Extract Peel-Off Gel Mask and Gel Serum - Ambarwati, Neneng Siti Silfi; Irtawidjajanti, Sri; Armandari, Mari Okatini; Ana, Elsa Fitri; Triyani, Yulia (Journal of Pharmaceuticals and Natural Sciences, 2025)
The cosmetics industry is experiencing rapid growth as consumer awareness of the importance of safe and effective skincare products increases. This creates an excellent opportunity for natural ingredient cosmetics. Garcinia dulcis (Roxb.) Kurz has been proven to have bioactive activities, such as antioxidants and anti-elastase, which can potentially be used for skin care, such as preventing premature aging and maintaining skin elasticity. This study evaluates consumer preference levels for peel-off masks and Garcinia dulcis extract serums. The method used was a hedonic test with parameters of aroma, skin feel, texture, color, absorption, viscosity, and drying time on a scale of 1-5. Data were analyzed using the Mann-Whitney U test. The results were that 33.85% of the panelists were neutral towards the serum’s aroma, and 40% did not like the mask’s aroma. A total of 41.54% of the panelists liked the serum’s texture, and 33.85% of the panelists were neutral about liking the mask’s texture. The skin taste parameter showed that 58.46% of the panelists liked the serum, and 36.92% were neutral to liking the mask. The gel serum and peel-off gel mask colors were liked by 46.15% and 44.62% of the panelists, respectively. The gel serum’s absorption rate and the peel-off gel mask’s drying time were liked by 36.92% and 33.85% of the panelists, respectively. 33.85% of the panelists liked the gel serum’s viscosity. The statistical test showed significant differences in aroma, taste, and absorption (p < 0.05). In conclusion, the peel-off gel mask and serum of Garcinia dulcis (Roxb.) Kurz extract has good potential as a skincare product, although further development is needed to improve the aroma, taste, and drying time.